Characterization of Aluminum powders I. Parameters of reactivityof Aluminum powders; Propellants, Explosives, Pyrotechnics; Vol. 27, № 6 - Ilyin A. P. Aleksandr Petrovich; Gromov A. A. Aleksandr Aleksandrovich; An V. V. Vladimir Vilorievich; Faubert F. Francois (2002, 2002)
Title screen